Teaching turbulent flow through pipe fittings using computational fluid dynamics approach. Issue 1 (2nd January 2020) - Gajbhiye, Bhavesh D.; Kulkarni, Harshawardhan A.; Tiwari, Shashank S.; Mathpati, Channamallikarjun S.
Abstract : The largest network of fluid transportation in the world is through pipelines. During the transportation of fluids through pipes, several "fittings" are used in the piping system such as elbows, T‐junctions, reducers, expanders, bends, couplings, valves, etc. The flow complexities in pipe fittings are accounted for the pressure drop in piping network design. The pressure drop is estimated using the loss coefficient or equivalent length method using standard charts. Computational fluid dynamics (CFD) is a reliable tool to estimate pressure drop and understand nonidealities in pipe fittings. The use of CFD in the advanced level course in transport phenomena/fluid flow for piping network design can help students to implement modern mathematical tools as well as evaluate standard protocols followed in the industries. In this article, an interactive teaching methodology has been implemented to investigate the hydrodynamics in various pipe fittings (elbow, bend, Tee, and reducer) by actually visualizing the flow. The three‐dimensional flow visualization is used to demonstrate the nonidealities such as separation, swirling, dead zones, etc. The CFD simulations of pipe fittings provided a new learning experience to the students that would help them to predict the pressure drops in industrial piping network systems. The outcome from the students' survey showed that the proposed CFD methodology assisted them to gain a better understanding of conventional Chemical Engineering subjects of "Transport Phenomena" and "Fluid Dynamics" in an innovative way. Abstract : The CFD simulations of pipe fittings provided a new learning experience to the students that would help them to predict the pressure drops in industrial piping network systems. The outcome from the students' survey showed that the proposed CFD methodology assisted them to gain a better understanding of conventional Chemical Engineering subjects of 'Transport Phenomena' and 'Fluid Dynamics' in an innovative way.